Minimization of Fuzzy Rule Base by Using Fuzzy Switching Function - Najim Abdul Ameer, Ahlam; A.J. Al-Ghubainy, Maicem (Journal of Engineering and Sustainable Development, 2010)
This paper present the general technique in a new application, it will be used to reduce the number of fuzzy rule base to reduce the time of applications and simplify its form.This method will be applied for the controller of helicopter module.